Case report: Acute dyspnea secondary to urinothorax following ureteroscopy - Andrew McLean; Marc T. Bartman; Elizabeth B. Winton (Urology Case Reports, 2023)
A 63-year-old female presented with a tension urinothorax after pyeloscopy, lithotripsy, and percutaneous nephrolithotomy that manifested as dyspnea and abdominal pain. CT Thorax demonstrated a large right pleural effusion with middle and lower lobe collapse with leftward shift concerning for tension hydrothorax. Analysis of the effusion after pigtail catheter demonstrated an exudative effusion with resultant resolution of the effusion after a 5-day hospital course. This case illustrates a uniquely rare complication of percutaneous urologic intervention. We highlight this case to stress the importance of considering urinothorax as a cause for dyspnea and abdominal pain after renal and ureteric interventions.